2021
DOI: 10.1183/23120541.00324-2021
|View full text |Cite
|
Sign up to set email alerts
|

Higher alveolar deposition of particulate matter in emphysematous lobes of COPD

Abstract: Emphysema can be examined quantitatively on high-resolution computed tomography (HRCT) by measuring the low-attenuation areas of the lung and has been associated with decrease in lung function in patients with COPD [1]. Previous studies have associated levels of air pollution with emphysema severity of the total lung [2, 3]. However, the relationship between inhaled particulate matter (PM) deposition in the lungs and the degree of emphysema at the lung lobar level remains poorly understood. We examined the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In this study, we observed that an increase in PM 2.5 , NO 2 , and O 3 was associated with greater increases in upper lobe LAA than in lower lobe LAA. This was consistent with a previous study showing that PM 2.5 deposition was associated with higher emphysema severity in upper lobes than in lower lobes ( 61 ). This suggested that upper lobes might be preferentially impacted by air pollution than lower lobes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we observed that an increase in PM 2.5 , NO 2 , and O 3 was associated with greater increases in upper lobe LAA than in lower lobe LAA. This was consistent with a previous study showing that PM 2.5 deposition was associated with higher emphysema severity in upper lobes than in lower lobes ( 61 ). This suggested that upper lobes might be preferentially impacted by air pollution than lower lobes.…”
Section: Discussionsupporting
confidence: 94%
“…Our results further showed that air pollution was associated with lobar emphysema, especially in the upper lobes, by PM 2.5 , NO 2 , and O 3 . Our previous study found that a 1 μg/m 3 increase in PM 2.5 deposition in each lung lobe was associated with increases in %LAA (beta coefficient) of the same lung lobe ( p < 0.05) ( 61 ). Because of particle physicochemical characteristics, lung geometric difference, and breathing pattern, the associations between air pollutants with lung lobe percent emphysema could be associated with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although air pollution variables appear to correlate well with the increased COPD prevalence and declining pulmonary function [39][40][41], less is known about the association with O 2 desaturation during exercise in emphysematous patients. Our previous study found that air pollution (PM 2.5 , NO 2 , and O 3 ) was associated with lobar emphysema, especially in the upper lobes (p < 0.05) [42]. PM 2.5 can penetrate deeply into the lungs and destroy alveolar septa by generating excessive reactive oxygen species (ROS) [43].…”
Section: Discussionmentioning
confidence: 99%